2008
DOI: 10.2337/dc07-2349
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Complications in Youth

Abstract: OBJECTIVE -Youth with type 1 diabetes face long-term risks of health complications of the disease. Little is known about patients' and parents' knowledge, acquisition of information, and family communication regarding these complications. This paper reports qualitative analyses of parental focus-group discussions of this topic.RESEARCH DESIGN AND METHODS -A total of 47 participants (30 mothers, 14 fathers, and 3 others) representing 33 children between the ages of 8 and 18 years with type 1 diabetes participat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
59
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(65 citation statements)
references
References 14 publications
6
59
0
Order By: Relevance
“…6 Similar findings are seen in previous studies where there is a high prevalence of diabetes among the elders. 7,8 Many patients are illiterate in our study group, as educational level is positively associated with knowledge of the disease. 9 Similar finding was seen in a study done in rural area of Chennai, which reports that the higher the educational levels, the higher the knowledge about diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…6 Similar findings are seen in previous studies where there is a high prevalence of diabetes among the elders. 7,8 Many patients are illiterate in our study group, as educational level is positively associated with knowledge of the disease. 9 Similar finding was seen in a study done in rural area of Chennai, which reports that the higher the educational levels, the higher the knowledge about diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Misinformation was reported elsewhere in the literature (Buckloh et al 2008). Buckloh et al (2008) also reported on the negative impact that a lack of information or withholding information can have leading to misunderstanding about the illness and possible maladjustment.…”
Section: "Even When You Access Medical Services or You Know You Speamentioning
confidence: 99%
“…Buckloh et al (2008) also reported on the negative impact that a lack of information or withholding information can have leading to misunderstanding about the illness and possible maladjustment. A number of the young people reported that the lack of information and support had a negative impact on their health and wellbeing, and the ability to cope with their condition:…”
Section: "Even When You Access Medical Services or You Know You Speamentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10][11] At the root of tensions are the negotiation of children's autonomy as adolescents; differing opinions on each party's role; children's irritation at parents' frequent reminders, lack of knowledge, and scepticism of their ability to manage diabetes; and parents' frustration with nonadherence. 5,9,[11][12][13][14][15] These struggles have serious repercussions; conflict compromises family cohesion, adherence and control, intra-family communication, and the quality of life (QOL) and physical and psychosocial functioning of parents and children. 5,7,[16][17][18] There are limited data on Jamaican youth living with diabetes.…”
mentioning
confidence: 99%